2011
DOI: 10.1111/j.1708-8240.2011.00479.x
|View full text |Cite
|
Sign up to set email alerts
|

Nightguard Vital Bleaching: Side Effects and Patient Satisfaction 10 to 17 Years Post‐Treatment

Abstract: Nightguard vital bleaching provides patient satisfaction with minimal side effects up to 17 years post-treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 23 publications
1
26
0
1
Order By: Relevance
“…The 10% CP gel has been considered a safe bleaching technique for tooth structure, since several studies demonstrated low incidence of post-operative sensitivity (8) and low trans-enamel and trans-dentinal cytotoxicity (4). A recent in vivo study also demonstrated that nightguard vital bleaching with 10% CP gel provides patient satisfaction with minimal side effects up to 17 years posttreatment (9). However, some patients complain about the long treatment time required for this technique.…”
Section: Introductionmentioning
confidence: 99%
“…The 10% CP gel has been considered a safe bleaching technique for tooth structure, since several studies demonstrated low incidence of post-operative sensitivity (8) and low trans-enamel and trans-dentinal cytotoxicity (4). A recent in vivo study also demonstrated that nightguard vital bleaching with 10% CP gel provides patient satisfaction with minimal side effects up to 17 years posttreatment (9). However, some patients complain about the long treatment time required for this technique.…”
Section: Introductionmentioning
confidence: 99%
“…In general, as cited by Attin et al (5), this technique uses low-concentration peroxide-containing agents generally with a low cost individual tray for 2-4 weeks and application intervals of 4-8 h per day. A 10-17 years follow-up study (4) showed that home bleaching provided patient satisfaction with minimal side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Different techniques may be employed for brightening discolored teeth, such as: home bleaching, in-office bleaching or a combination of both (2). Since its introduction by Haywood and Heymann (3), home bleaching has become an attractive treatment modality for patients and dentists due to its excellent clinical effectiveness, easy application, lower cost and safety of the used materials (1,4). In general, as cited by Attin et al (5), this technique uses low-concentration peroxide-containing agents generally with a low cost individual tray for 2-4 weeks and application intervals of 4-8 h per day.…”
Section: Introductionmentioning
confidence: 99%
“…However, this technique has several limitations, such as the fact that the professional does not directly supervise the entire treatment and the long bleaching time needed to achieve significant color improvement as well as the risk of gel application over exposed dentin and soft tissue [10]. Therefore, alternative professional bleaching therapies, with the goal of minimizing the toxic effect on pulp cells, have been the target of diverse contemporary researches [4,8].…”
Section: Introductionmentioning
confidence: 99%
“…Up to the present time, at-home bleaching using 10 % carbamide peroxide (CP) has been considered the safest bleaching therapy for the pulp-dentin complex [8][9][10][11]. However, this technique has several limitations, such as the fact that the professional does not directly supervise the entire treatment and the long bleaching time needed to achieve significant color improvement as well as the risk of gel application over exposed dentin and soft tissue [10].…”
Section: Introductionmentioning
confidence: 99%